2011
DOI: 10.3767/003158511x617381
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing Vermisporium (Amphisphaeriaceae), a genus of foliar pathogens of eucalypts

Abstract: The genus Vermisporium presently accommodates 13 species, 11 of which are associated with leaf spots of eucalypts in the Southern Hemisphere. Vermisporium is chiefly distinguished from Seimatosporium (Amphisphaeriaceae) on the basis of a short exogenous basal appendage, and the absence of a recognisable apical appendage. Due to the increasing importance of these species in native forests, and confusion pertaining to their taxonomy, a revision of the genus was undertaken based on fresh collections and dried her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…multiple appendages in lineages ii and v; appendages absent in lineages i and iv). Previous generic circumscriptions of these coelomycetes based on conidial appendages alone are not well supported, a finding which was also recently observed among other genera of appendaged coelomycetes (Barber et al 2011, Crous et al 2012). The type species of Kellermania , K. yuccigena , and Piptarthron , P. macrosporum ( ≡ K. macrospora ), belong to separate lineages ii and i, respectively, that notably form a clade (pp = 0.89) with K. unilocularis in the ITS analysis (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…multiple appendages in lineages ii and v; appendages absent in lineages i and iv). Previous generic circumscriptions of these coelomycetes based on conidial appendages alone are not well supported, a finding which was also recently observed among other genera of appendaged coelomycetes (Barber et al 2011, Crous et al 2012). The type species of Kellermania , K. yuccigena , and Piptarthron , P. macrosporum ( ≡ K. macrospora ), belong to separate lineages ii and i, respectively, that notably form a clade (pp = 0.89) with K. unilocularis in the ITS analysis (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…with Discostroma sexual morphs. Barber et al (2011) and Tanaka et al (2011) also showed that both Seimatosporium and Discostroma cluster in a monophyletic clade in their molecular data analyses. However, both genera lack molecular data for their type species (Tanaka et al 2011), thus we prefer to maintain both names until the link is proven by molecular analyses.…”
Section: Resultsmentioning
confidence: 86%
“…Swart have long, falcate, fusiform or sigmoid conidia with 3-4-septa, rarely 5-septa, and basal appendages. These species were excluded from Seimatosporium and included in Vermisporium based on their morphology and phylogeny (Barber et al 2011). Therefore we introduce Seimatosporium rhombisporum as a new species considering both morphology and phylogeny.…”
Section: Resultsmentioning
confidence: 99%
“…Almeida & Sousa da Câmara) Nag Raj are 3-celled conidial forms that Nag Raj (1993) placed in Pestalotiopsis, but which actually belong in Truncatella . LSU sequence data reveal that Truncatella is a distinct genus in the family Amphisphaeriaceae (Jeewon et al 2002;Barber et al 2011;Maharachchikumbura et al 2014). …”
Section: Orders Of Sordariomycetesmentioning
confidence: 97%
“…Vermisporium was chiefly distinguished from Seimatosporium on the basis of a short exogenous basal appendage, and the absence of a recognisable apical appendage. Barber et al (2011) showed the genus to be a synonym of Seimatosporium based on DNA sequence data analysis of the nrDNA-ITS and 28S nrRNA genes, and transferred eight species to Seimatosporium.…”
Section: Tubakiellamentioning
confidence: 99%